Molecular Mechanism of Oil-Infused Silicone Preventing Mussel Biofouling - Jian He; Jiawei Li; Yihan Sun; Yuanyuan Shen; Qi Wei; Dun Zhang; Danqing Feng; Peng Wang (Research)
Marine biofouling causes severe economical and environmental challenges to marine industries and maritime activities. Biofouling prevention has emerged as one of the most pressing issues in water-related industries. Recently, the slippery liquid-infused porous surfaces (SLIPSs) have shown great potential for biofouling prevention across a broad spectrum of fouling organisms. However, our understanding of the mechanisms by which SLIPSs prevent biofouling remains limited. In this study, we discovered that oil-infused polydimethylsiloxane elastomer (i-PDMS), a silicone-based SLIPS variant, significantly inhibited the sensory responses of the fouling mussel Mytilopsis sallei, particularly at its sensory organ, the foot. Using bioinformatics and molecular biology analyses, we demonstrated that i-PDMS disrupts larval settlement of M. sallei by interfering with the mechanosensitive transient receptor potential melastatin-subfamily member 7 (TRPM7) channel, which is highly expressed in the foot during the settlement process. Furthermore, adhesion assays and molecular dynamics simulations revealed that the secreted foot proteins of the mussel are unable to effectively interact with the i-PDMS surface due to nanoscale fluctuations at the material interface. These findings enhance our understanding of how fouling organisms sense and adhere to surfaces and provide deeper insights into the antifouling mechanisms of SLIPS.